From environment to lung: A literature review on exposure risk factors and prevention of Aspergilosis - Asriyani Abdullah; Insani Fitrahulil Jannah; Elfira Buamona (Indonesian Journal of Health Science, 2026)
Aspergillosis comprises a spectrum of pulmonary diseases caused by inhalation of Aspergillus spores from the environment in individuals with immunological vulnerability or structural lung damage. This review summarizes major environmental sources of exposure (soil, compost, hospital ventilation and water systems, and construction activities), key host and environmental risk factors, and environmental and clinical prevention strategies. Multiple studies report increased airborne spore counts and higher incidence of invasive aspergillosis among haematology patients during hospital construction when protective ventilation and HEPA filtration are insufficient. Principal host risk factors include prolonged neutropenia, haematological malignancies, transplantation, immunosuppressive therapy, post‑tuberculosis cavities, severe COPD, and other chronic lung diseases. Climate change and natural disasters are thought to enhance the distribution of airborne fungal spores, although quantitative data specifically linking these events to aspergillosis remain limited. Effective prevention requires an integrated approach combining environmental control, targeted antifungal prophylaxis, screening in patients with structural lung disease, patient education, and stewardship to address azole resistance within a One Health framework.